Revisiting attitude towards advertising, its antecedent and outcome: A two-stage approach using PLS-SEM - Ting, H. (Universita Putra Malaysia, 2015)
Attitude towards advertising, its antecedent and outcome are welldocumented in advertising literature. Moreover, the theory of reasoned action is often used to support the relationships between belief, attitude and intention towards advertising, especially in the western context. However, little is done to attest the dimensionality of belief factors in explaining attitude and intention towards advertising in the developing markets. Consequently, misspecification of model and omission of measures due to deficiencies in analysis may likely lead to irrelevant conclusion to knowledge and practices. Hence, the present study is aimed to revisit the belief-attitude-intention model in advertising research using two-stage approach in PLS-SEM. Belief factors are constructed as formative measurement to form personal and societal belief factors in higher order component model. Questionnaire-based survey was administered at universities in Malaysia and 347 respondents were subsequently sampled. The findings show that attitude of Malaysian young consumers towards advertising is formed by both positive and negative beliefs. In particular, personal belief factors are found to have greater impact on their attitude and intention than societal belief factors.